Cultivo descontínuo alimentado de Bacillus firmusna produção da enzima Ciclomaltodextrina Glucano-Transferase (CGTase) - Bueno, Maicon Ramon (2014)
The Cyclomaltodextrin Glucanotransferase enzyme (CGTase) is industrially important due to the fact of being the only enzyme in production of cyclodextrins (CDs). The CDs belongs to the family macrocyclic oligosaccharides that are capable to form complexes of receptor-substrate type, with the ability to form inclusion complex with a variety of substances which have their properties changed by complexation, this is the main reason why CDs are been widely used in industrial, technological products and in analytical methods, pharmaceutical drugs, foods or cosmetics. The aim of this dissertation was to study the kinetics involved in obtaining the CGTase enzyme in a fed batch process by the synthesis of cyclodextrins, using starch as substrate and the Bacillus firmus Strain 37 micro-organism, and evaluate the cell growth responses, enzymatic activity and other variables involved in the fermentation process. The fermentation tests were performed in Bioflo III reactor operating in batch and fed-batch, for obtaining the parameters such as pH, temperature, dosages substrates, substrate consumption, production of soluble proteins, and among others, in order to improve the activity of the CGTase enzyme with the bacterial yield. Were also performed discontinuous tests in shaking incubator (shaker) for further comparison of results. The culture medium for bacterial growth was based on previous studies of different authors using the standard medium of Horikoshi and its modifications. In this study, we performed a total of nine sets of tests in different conditions by varying the substrate type, the concentration of yeast extract and cultivation time. For the synthesis of CDs by the CGTase enzyme using soluble starch and the commercial starch, it was observed that the commercial starch showed slightly higher values mainly in relation to the production of γ-CD. The better results obtained for the production of CGTase enzyme in γ-CD synthesis were observed in tests where starch pulses were applied and feedback of the medium, among the tests, the test 7, with approximately 0.26 U/mL for γ-CD and a lower yield was obtained for β-CD, about 0.04 U/ml. For production of CGTase in β-CD synthesis, the better result was observed in the test where there was no feedback and no starch pulses applied (Test 3) about 0.12 U / mL, however the production of CGTase for γ-CD synthesis was the less effective of all test performed, about 0.02 U/ ml. Thus, was observed that the batch or fed-batch in the biorretor operation influences the production of several CGTase enzymes, as well as the composition of the medium used also showed influence, particularly on the variation of yeast extract concentration. In previous studies, it was verified that Bacillus firmus Strain 37 is capable to produce preferably β-CD, however, in this study observed a positive effect on the production of γ-CD in the tests with feedback of the culture medium and also in tests with application of starch pulses, this advantageous effect may be considered, since the γ-CD exhibit a higher commercial value due to the ability to include larger molecules.